A simple numerical simulation method for unsaturated stratum under the water environmental load. (February 2023) - Li, Xiaoqiang; Lu, Dechun; Lin, Qingtao; Kong, Fanchao; Du, Xiuli
Abstract: A simple numerical simulation method is proposed to investigate the mechanical response of the unsaturated stratum under the water environmental load. The proposed numerical simulation method applies the water environmental load to the unsaturated stratum as the load condition, and adopts the developed non-orthogonal elastoplastic constitutive model for unsaturated soil to describe the mechanical behaviors at the material scale. The mechanical response of unsaturated stratum is obtained by solving the discretized governing equation of the mechanical equilibrium. The proposed numerical simulation method is implemented based on the commercial finite element software ABAQUS. The effectiveness of the proposed method is verified through the element tests on the Botkin silt, the element tests on the Pearl clay, and a model test of the rising water level on a sand column. The numerical simulations of the rising and decreasing groundwater level in the unsaturated stratum are conducted. During the rising groundwater level, the non-collapsible stratum produces rebound deformation, the collapsible stratum below the groundwater level occurs rebound deformation, and the collapsible stratum above the groundwater level mainly produces settlement deformation. During the decreasing groundwater level, both the collapsible stratum and the non-collapsible stratum produce the settlement deformation.